1991
DOI: 10.1177/106591299104400112
|View full text |Cite
|
Sign up to set email alerts
|

Politicized Group Identification: the Case of Fundamentalism

Abstract: or many citizens, group identifications provide cognitive struc-M~ tures through which the political world can be viewed. Grouprelated attitudes seem to be important means by which political beliefs can be organized and evaluated. The decade of the eighties has seen a renewed research emphasis on the political importance of group identifications. (See especially Conover 1985;Leege et al. 1989;Klein 1984; Guth et al., 1988;and Price 1989). Conover and Feldman (1981) have argued that group attitudes are the prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Consequently, it appeared to us that the best way to capture this process would be to investigate the impact of our explanatory and control variables for different groups of Muslim Americans defined by how our respondents identified themselves. See, e.g., Abdelal et al (2006);Conover (1984); Jelen (1991); Koch (1993); Wilcox (1989). 18 One aspect of this involves how religious institutions help mobilise members, and this influence will naturally have a greater impact on those who are more religiously committed.…”
Section: Notesmentioning
confidence: 99%
“…Consequently, it appeared to us that the best way to capture this process would be to investigate the impact of our explanatory and control variables for different groups of Muslim Americans defined by how our respondents identified themselves. See, e.g., Abdelal et al (2006);Conover (1984); Jelen (1991); Koch (1993); Wilcox (1989). 18 One aspect of this involves how religious institutions help mobilise members, and this influence will naturally have a greater impact on those who are more religiously committed.…”
Section: Notesmentioning
confidence: 99%
“…Religious self-identifications have also been shown to have positive benefits in analyzing mass opinion. Studies have found that the religious "fundamentalist" self-identification offers insight about religious groups and political behavior (Jelen 1991;Kellstedt and Smidt 1991). Other analyses conclude that identification with a religious movement, such as fundamentalism, may supplement classification by tradition, though it would not be an appropriate proxy measure for belonging (Smidt, Kellstedt, and Guth 2009).…”
Section: The Value Of Religious Self-identificationmentioning
confidence: 99%
“…Similar to the relationship between religious self-identification and group preferences, previous research provides evidence of the political nature of religious identification. Identification with a religious subculture may both affect and reflect an individual's social and political views (Edgell and Tranby 2007;Jelen 1991;Kellstedt and Smidt 1991), though it should be noted that self-identification does not reflect monolithic political persuasions. Also, political behaviors and attitudes and the ways in which evangelicals engage political issues and employ political resources (e.g., values, ideology, and practices) may vary as a result of religious subcultural association (Hecht 2001).…”
Section: Religious Self-identifications and Political Preferencesmentioning
confidence: 99%
“…For all three sets of groups, there exists considerable research about the sizable gaps in opinion for certain issue domains between the groups (Conover 1988;Jelen 1991;Kaufman and Petrocik 1999;Kellstedt and Corwin 1991;Kellstedt et al 1994;Kinder and Sanders 1996;Page and Shapiro 1992;Smidt 1988). In the case of gender, men and women have different views of policies involving the use of violence and compassion issues.…”
Section: Selection Of Groupsmentioning
confidence: 99%
“…When one compares the percent of African Americans in Congress to national population estimates (12.8% in 2 0 0 0 ), one finds even greater disparity between the two racial groups. (Jelen 1991;Kellstedt and Corwin 1991;Kellstedt et al 1994;Smidt 1988). Meanwhile, mainline Protestants largely appear to be mirror opposites in their policy attitudes, which stem from their less literalistic view of the scripture, a more accepting attitude toward homosexuals as seen in their willingness to debate the issue of ordination of homosexuals, and a readiness to allow women to assume leadership roles within the church (Hunter 1990;Wuthnow 1988).…”
Section: Selection Of Groupsmentioning
confidence: 99%